(untitled) (Revista LABVERDE, 2011)
This study aims to diagnose the environmental characteristics University City and Butantan Institute area, located in the West Zone of São Paulo, as well as its surroundings, to propose improvements based on environmental concepts of green infrastructure and transport clean and show how these factors contribute to mitigate the negative effects of heat island in environmental design.